Magnetic properties of pulverized titanomagnetite, Fe2.4 Ti0.6 O4 : effect of thermal fluctuations - Brown, A. P.; O’Reilly, W. (Geophysical journal international, 1999)
The magnetic properties of titanomagnetite, Fe2.4 Ti0.6 O4 , pulverized in a ball mill for times between 3.5 and 78 hr form a consistent picture if the material is treated as monodomain particles of decreasing size progressively subject to thermal fluctuations. The magnetic observations are made over a range of characteristic measurement times: 10−3 s (susceptibility measurement), 1 s (coercive force measurement) and 104 s (viscous decay of remanence). The magnetic viscosity coefficient first rises then falls as pulverization proceeds. This is ascribed to a distribution of time constants in the assemblage of particles, the maximum viscosity occurring when the value of the time constant at the peak in the distribution, in zero field, is the same as the characteristic measurement time. The application of a field equal to the coercive force shifts the distribution so that the peak corresponds to the characteristic time of the coercive force measurement. The position of the corresponding zero‐field peak can readily be calculated from the observed coercive force and the uniaxial anisotropy constant derived from hysteresis loop parameters. This shows that the calculated zero‐field peak position for the degree of pulverization at which the maximum viscosity occurs is the same as the viscous decay measurement time. At maximum pulverization time, and therefore smallest particle size, the peak in the zero‐field time constant distribution is five orders of magnitude bigger than the characteristic time of susceptibility measurement, which can be satisfactorily interpreted in terms of only a few per cent of the particle assemblage being affected by thermal fluctuations. The observed effectiveness of thermal fluctuations requires that the pulverized particles contain nanocrystals, in size about two orders of magnitude smaller than the particle envelope. The presence of the nanocrystals is supported by transmission electron microscope and X‐ray line broadening observations.